Uji Antagonisme Trichoderma harzianum Dan Azotobacter chroococcum Terhadap Rhyzoctonia solani, Sclerotium rolfsii dan Fusarium oxysporum secara in-vitro - A. Marthin Kalay; Abraham Talahaturuson; Wilhemina Rumahlewang (Agrologia, 2018)
Damage to plants by pathogenic fungi is often found in nurseries and field. Biological control offers a promising alternative for managing diseases in plants because they are environmentally friendly compared to pesticides. The aim of the study was to test the power of the antagonism of Trichoderma harzianum and Azotobacter chroococcum on solid organic media "TRIAZOTE"  which had been stored for five months against R. solani, S. rolfsii, and F. oxysporium pathogens. In-vitro treatment tested the power of antagonism of T. harzianum and A. chroococcum on growth of R. solani, S. rolfsii, and F. Oxysporum pathogens. The results showed that T. harzianum in "TRIAZOTE" which had been stored for five months could inhibit pathogenic growth R. solani, S. rolfsii, and F. oxysporum by 54.57%, 66.22%, and 68,57% respectively. While A. chroococcum did not significantly inhibit pathogenic growth of R. solani (11.02%), S. rolfsii (9.09%) and F. oxyprorum (10.99%). To control the disease in plants, especially those caused by soil borne pathogens R. solani, S. rolfsii and F. oxyprorum, can use biological fertilizer "TRIAZOTE" even though it has been stored for five months